Discharged Energy Properties of SrO–PbO–Na2O–Nb2O5–SiO2 Glass‐Ceramics with Different Crystallization Time. Issue 2 (15th December 2014) - Zhang, Qingmeng; Li, Chang; Liu, Hongwei; Tang, Qun; Liu, Jinfeng; Li, Hongtao; Wang, Meng; Xie, Weiping; Du, Jun; Rodrigue, A. C.
<x xml:space="preserve">Abstract</x> Discharged energy properties of PbO–SrO–Na2O–Nb2O5–SiO2 glass‐ceramics with crystallization time from 1 to 1000 min were investigated by measuring their hysteresis loops (described as quasi‐static measuring method) and pulse‐discharge current‐time curves (described as dynamic measuring method). The results show the same trend for both measuring methods: With the increment of crystallization time, the discharged energy density increases gradually, while the energy efficiency decreases. The highest energy efficiencies were obtained in the sample with crystallization time of 1 min, which are 96.3% and 82.4%, corresponding quasi‐static and dynamic measurement, respectively. The reduction of energy efficiency with crystallization time is attributed to combined effect of ferroelectric polarization and interfacial polarization, and part of the corresponding energy could not release in the pulse‐discharge process.